Comparison of Attitudes, Beliefs, and Resource-seeking Behavior for CAM Among First- and Third-Year Czech Pharmacy Students - Pokladnikova, Jitka (American Journal of Pharmaceutical Education, 2008)
OBJECTIVES: To assess and compare first- and third-year Czech pharmacy students' attitudes toward CAM, CAM use, CAM evidence, recommending CAM to patients, and including CAM in the pharmacy curricula. METHODS: The CAM Health Belief Questionnaire (CHBQ) was translated from English to Czech and administered to 250 first-year and 187 third-year students. RESULTS: The students' mean CHBQ score was 48.5, affirming positive attitudes toward CAM. Vitamins, herbs, massage, and relaxation were the most commonly used therapies among students. Czech students reported significantly low use of evidence-based resources on CAM. Ninety percent of the pharmacy students surveyed would recommend CAM and 89% believed pharmacists should be knowledgeable of CAM. Ninety-one percent of first-year vs 78% of third-year students supported CAM education (p = 0.01). CONCLUSIONS: Czech students have positive attitudes about CAM, but are less likely to access evidence-based information. They agree pharmacists should be educated about CAM.